2018
DOI: 10.1370/afm.2247
|View full text |Cite
|
Sign up to set email alerts
|

Finance and Time Use Implications of Team Documentation for Primary Care: A Microsimulation

Abstract: Financial viability of team documentation under fee-for-service payment may require more physician time to be reallocated to patient encounters than under a capitated payment model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…A microsimulation of the cost of scribes showed that primary care providers would need to increase visits by 8% in fee-for-service models. 23 This is consistent with the visit increases reported in the studies 26 and statements of provider willingness to see 1 more patient per shift to help offset costs. 20 , 21 Given that providers who use a scribe may not experience the same gains in net revenue compared with those who do not, 28 practices may be reluctant to invest in scribes which can cost $33,600 or more in the first year when factoring in start-up and opportunity costs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A microsimulation of the cost of scribes showed that primary care providers would need to increase visits by 8% in fee-for-service models. 23 This is consistent with the visit increases reported in the studies 26 and statements of provider willingness to see 1 more patient per shift to help offset costs. 20 , 21 Given that providers who use a scribe may not experience the same gains in net revenue compared with those who do not, 28 practices may be reluctant to invest in scribes which can cost $33,600 or more in the first year when factoring in start-up and opportunity costs.…”
Section: Discussionsupporting
confidence: 81%
“…Based on these costs, study authors found visit volume would need to increase by 7% (capitation) to 8% (fee for service) to achieve medical scribe net revenue neutrality, noting that volumes need to be higher in the first year of scribe implementation to meet this benchmark. 23 The literature provides evidence that scribes can yield a positive ROI, with 2 pilot studies reporting actual and projected ROIs of 30%, 27 and 112% 25 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50,57 In most cases, the information will be subsequently reviewed and approved by the provider, before it becomes part of the patient's permanent medical record. 20,24,25,43,44,48,[52][53][54]57,65,70,72,74,[83][84][85] In addition, medical scribes are involved in many other activities beyond scribing in the exam room. They are often asked to conduct "pre-charting" (ie, constructing in-progress notes before patient arrival based on historical information, such as summaries of past clinic visits and hospitalizations).…”
Section: Managementmentioning
confidence: 99%
“…17 A microsimulation model by Basu and colleagues estimates the conditions under which it would be financially viable to have a staff member enter patient history, place orders, and guide patients-in both feefor-service and capitated payment. 18 Three essays provide their own kinds of teachable moments. In light of the growing phenomenon of parttime practice, Bodenheimer sees ways that clinicians and practices can make a number of adjustments to foster continuity and relationships.…”
mentioning
confidence: 99%